Development and validation of an instrument to measure family physicians' clinical aptitude in metabolic syndrome in Mexico Desarrollo y validación de un instrumento para medir la aptitud clínica de médicos familiares en síndrome metabólico en México - Carlos E Cabrera-Pivaral; Clara Luz Gutiérrez-Ruvalcaba; Irma Concepción Peralta-Heredia; Carlos Alonso-Reynoso (Instituto Nacional de Salud Pública, 2008)
OBJECTIVE: The purpose of this work was to measure family physicians' clinical aptitude for the diagnosis and treatment of metabolic syndrome in a representative sample from six Family Medicine Units (UMF) at the Mexican Institute for Social Security (IMSS), in Guadalajara, Jalisco, México. MATERIAL AND METHODS: This is a cross-sectional study. A validated and structured instrument was used, with a confidence coefficient (Kuder-Richardson) of 0.95, that was applied to a representative sample of 90 family physicians throughout six UMFs in Guadalajara, between 2003 and 2004. Mann-Whitney's U and Kruskal-Wallis' tests were used to compare two or more groups, and the Perez-Viniegra Test was used to define aptitude development levels. RESULTS: No statistically significant differences were found in aptitude development between the six family medicine units groups and other comparative groups. CONCLUSIONS: The generally low level of clinical aptitude, and its indicators, reflects limitations on the part of family physicians at the IMSS in Jalisco to identify and manage metabolic syndrome. OBJETIVO: El propósito de este estudio fue medir la aptitud clínica de los médicos familiares de una muestra representativa de seis Unidades de Medicina Familiar (UMF) del Instituto Mexicano del Seguro Social (IMSS), en Guadalajara, Jalisco, México, en el diagnóstico y tratamiento del síndrome metabólico. MATERIAL Y MÉTODOS: Es un estudio observacional, prospectivo y comparativo. Se diseñó y validó un instrumento estructurado con un coeficiente de confianza (Kuder-Richardson) de 0.95, aplicado a una muestra representativa de 90 médicos familiares de seis UMF en Guadalajara, entre 2003 y 2004. Se utilizaron los tests de Mann-Whitney U y Kruskal-Wallis para comparar dos o más grupos, y el test de Pérez-Viniegra se utilizó para definir los niveles de desarrollo de aptitud. RESULTADOS: No se observaron diferencias significativas en el desarrollo de aptitud entre las seis UMF. CONCLUSIONES: El bajo nivel general de aptitud clínica refleja las limitaciones para identificar y manejar el síndrome metabólico por parte de los médicos familiares.